Rancang Bangun Modul Pembelajaran Bengkel Listrik - Sonong Sonong; Herman Nauwir; Muhammad Ruswandi Djalal (Muhammadiyah University, Sidoarjo, 2019)
Electric motor is an electric machine that has a function as a converter of electrical energy into mechanical energy. Electric motors are widely used as movers because they are better in terms of technical and economical, but have disadvantages such as large initial currents so that they cannot last long, to overcome this can be used Y-utan star starting method both manually and automatically created in a panel box. In the operation and manufacture of a protection system for a 3 phase induction motor, some supporting equipment can be arranged in a panel box so that motor performance can be maximized. The results of this tool design are in the form of a panel box in which there are three types of circuits, namely: 3 phase induction motor operation circuit with the starting Y-∆ automatically, reversing the direction of 3 phase induction motor rotation, and 3 phase induction motor operation in two places. Where the series is equipped with a protection system and can be operated manually and automatically.